Electrochemical CO2 Reduction: Commercial Innovations and Prospects - Swapnil Varhade; Avni Guruji; Chandani Singh; Giancarlo Cicero; Max García‐Melchor; Joost Helsen; Deepak Pant (ChemElectroChem)
Abstract Sustainability is an imperative requirement in this era, with electrocatalytic power into fuels technologies emerging as a significant route toward sustainable chemistry. One of the focus areas within the chemical industry is capture of carbon dioxide (CO2) and its electrochemical reduction (eCO2RR) into economically viable commodities through the utilization of renewable sources. Despite some specific eCO2RR technologies being poised for market introduction, the development of a comprehensive technology for eCO2RR remains a challenge. While certain technologies targeting specific eCO2RR products are on the verge of deployment, substantial efforts are still necessary to transition and establish presence in the market over conventional technologies. This review highlights recent technological advancements, fundamental studies, and the persisting challenges from an industrial perspective. We take a deep dive into the research methodologies, strategies, challenges, and advancements in the development of applications for eCO2RR. Specifically, three eCO2RR products – CO, HCOOH, and C2H4 – as promising candidates for implementation are elaborated based on techno‐economic considerations. Additionally, the review discusses the industrial blueprint for these products, aiming to streamline their path toward commercialization. The intent is to present the status of eCO2RR, offering insights into its potential transformation from a mere laboratory curiosity to a feasible technology for industrial chemical synthesis.